2012
DOI: 10.1186/1471-2091-13-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthase mediates dye translocation across liposomal membranes

Abstract: BackgroundHyaluronan (HA) is made at the plasma membrane and secreted into the extracellular medium or matrix by phospolipid-dependent hyaluronan synthase (HAS), which is active as a monomer. Since the mechanism by which HA is translocated across membranes is still unresolved, we assessed the presence of an intraprotein pore within HAS by adding purified Streptococcus equisimilis HAS (SeHAS) to liposomes preloaded with the fluorophore Cascade Blue (CB).ResultsCB translocation (efflux) was not observed with moc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The original proposal that HAS translocates the growing HA-UDP chain through an intra-protein pore (Tlapak-Simmons et al 1999a) has been verified (Hubbard et al 2012;Medina et al 2012). We now understand that HAS enzymes function either as monomers (Tlapak-Simmons et al 1998) or oligomers (Bart et al 2015) and their processive mechanism utilizes an intra-HAS pore or deep protein cleft (Kumari et al 2006) within the plasma membrane ( Figure 7) that serves simultaneously to retain and to translocate the growing HA-UDP chain to the cell exterior (Hubbard et al 2012;Medina et al 2012;Bi et al 2015;Weigel 2015). Many questions still remain regarding the mechanism of synthesis and what causes and controls HA release and HA product size.…”
Section: Discussionmentioning
confidence: 97%
“…The original proposal that HAS translocates the growing HA-UDP chain through an intra-protein pore (Tlapak-Simmons et al 1999a) has been verified (Hubbard et al 2012;Medina et al 2012). We now understand that HAS enzymes function either as monomers (Tlapak-Simmons et al 1998) or oligomers (Bart et al 2015) and their processive mechanism utilizes an intra-HAS pore or deep protein cleft (Kumari et al 2006) within the plasma membrane ( Figure 7) that serves simultaneously to retain and to translocate the growing HA-UDP chain to the cell exterior (Hubbard et al 2012;Medina et al 2012;Bi et al 2015;Weigel 2015). Many questions still remain regarding the mechanism of synthesis and what causes and controls HA release and HA product size.…”
Section: Discussionmentioning
confidence: 97%
“…Note that the synthesis of hyaluronic acid is done through repeated addition of one glucuronic acid and one N ‐acetylglucosamine to the nascent polydisaccharide as the molecule is extruded via ABC transporters or hyaluronic acid synthase into the extracellular space . The exported hyaluronic acid will be degraded by some of the hyaluronidases ( HYAL1–6 ) or by ROS into fragments of different sizes if it is not incorporated into extracellular matrices …”
Section: Hyaluronic Acid: a Key Facilitator Of Cell Proliferationmentioning
confidence: 99%
“…The relatively small size and few transmembrane domains of streptococcal HAS suggest that they cannot facilitate pore formation for translocation of the growing HA chain (Weigel, 2002). However, recent work showed that HAS derived from S. equisimilis (SeHAS; encoded by seHas) could mediate the release of the small fluorescent dye Cascade Blue from inside liposomes, and that mutations, which decreased HAS activity and HA MW in an earlier study, in one of its transmembrane domains resulted in reduced Cascade Blue efflux (Kumari, Baggenstoss, Parker, & Weigel, 2006;Medina, Lin, & Weigel, 2012). However, recent work showed that HAS derived from S. equisimilis (SeHAS; encoded by seHas) could mediate the release of the small fluorescent dye Cascade Blue from inside liposomes, and that mutations, which decreased HAS activity and HA MW in an earlier study, in one of its transmembrane domains resulted in reduced Cascade Blue efflux (Kumari, Baggenstoss, Parker, & Weigel, 2006;Medina, Lin, & Weigel, 2012).…”
Section: Introductionmentioning
confidence: 99%